Interpersonal Communication in Efforts to Overcome Loneliness Depression Without Couples - Rizki Nuriandini; Agus Naryoso, S.Sos, M.Si (Interaksi Online, 2016)
Each individual will want to live in pairs because they include social beings who always socialize with other people. But it turns out there are times when some of the people who live their lives by not having a partner. As a result of various feeling was felt by them, one of which is depression indicated by such characteristics often feel sad and empty in their daily lives, loss of interest or favor to the usual activities accomplishments, changes in sleep patterns and eating habits resulting in lower weight weight, insomnia or hypersomnia nearly every day, fatigue, difficulty concentrating and difficulty to determine a decision. This research is a qualitative descriptive study paradigm postpositivisme and phenomenology. The purpose of this study was to determine the trigger depression lonely without a partner, knowing the concept of a person who is depressed lonely without a partner and describe the interpersonal communication activities carried out by someone who does not have a partner in the effort to overcome depression lonely without a partner. The informants is a career woman who has aged adults late and did not have a partner, based in Semarang and Batang. Referring to Interpersonal Communication Theory, Self Concept Theory, Self Disclosure Theory and Relational Maintenance Theory, which discusses the importance of sharing things related to interpersonal communication in maintaining relationships. The results of this study indicate that the trigger for the onset of depression lonely without a mate is not someone special had to give time and attention in particular to the informants of this study when they feel tired and bored with the daily routine or while facing problems. The concept of self-informant lonely without a partner showed a positive self concept in which self-disclosure that they have with others even higher also their special partner that they have for a variety of stories about various things. Generally they have a friend as the person chosen to be a partner in sharing the story because of their closeness and comfort they feel when compared with the family.